HANDBOOK OF UNIVERSITY AND PROFESSIONAL CAREERS IN SCHOOL PSYCHOLOGY - Floyd, Randy G., 1971-; Eckert, Tanya L. ([S.l.] : ROUTLEDGE, 2020)
The Handbook of University and Professional Careers in School Psychology is a comprehensive resource for school psychologists in doctoral training or currently appointed to positions in universities and other clinical professional settings. Across 30 unique chapters, experts in the field offer diverse, experienced perspectives on accessing resources, building skills, navigating difficult experiences, and flourishing in all major facets of the profession. The book places special emphasis on development throughout the career lifespan and the empowerment of women, people of color, and scholars from outside of the United States.
OCLC-licensed vendor bibliographic record.
Keywords: EDUCATION / Educational Psychology; EDUCATION / Counseling / General; School psychology -- Vocational guidance